A randomized comparative study between low-dose magnesium sulphate and standard dose regimen for management of eclampsia - Sahu, Latika; Singh, Shubhra; Tempe, Anjali; Koner, B. C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Eclampsia is a hypertensive disorder related to pregnancy, in which there is occurrence of one or more generalized convulsions and or coma, in the absence of other neurologic conditions. It is a common obstetric emergency. It contributes significantly to maternal and perinatal morbidity and mortality. Dr. J. A. Pritchard in 1955, introduced magnesium sulphate for control of convulsions in eclampsia and is used worldwide. Considering the low body mass index of Indian women, a low dose magnesium sulphate regime has been introduced by some authors. The Objective was to compare the efficacy of low dose magnesium sulphate regimen with standard Pritchard’s regimen for eclampsia. Methods: A prospective randomized study of fifty eclampsia cases, treated with magnesium sulphate (25 each with low dose regime and Pritchard regime) was carried out from October 2010 to January 2012 at MAMC & LNH, New Delhi, India. Results were analysed using Statistical Package of Social Sciences (SPSS) software 17.0. Results: In the present study, convulsions were controlled in 96% of eclampsia cases with low dose magnesium sulphate regimen. One case i.e. 4% had single episode of recurrence of convulsion, which was controlled by giving additional drugs and shifted to standard dose regimen. There was no maternal mortality. Conclusions: The maternal and perinatal morbidity and mortality in the present study were comparable to those of standard Pritchard’s regimen. The study did not find a single case of magnesium related toxicity with low dose magnesium sulphate regimen. Low dose magnesium sulphate regimen was found to be safe and effective in eclampsia.